Students’ Smoking Behavior and its Prevention Study on State Senior High School and State Vocational School Painan at South Pesisir Region - Zulkifli Zulkifli; Prayitno Prayitno; Marjohan Marjohan (Universitas Negeri Padang, 2018)
The background of this research was formulated in relation to student’s smoking behavior and aiming for: (1) grouping the students based on theirsmoking behavior; (2) achieving scores of three variables, which are the quality of the students smoking, the environmental quality of the non-smoking area, and the quality of information services by teacher guidance and couseling, and the differences and relation between the three variables and (3) effortsto prevent students smoking behavior by guidance and counseling teacher by using information services.This research used descriptive-quantitative method, and the populationwas the students and guidance and cunseling teacher in SMAN and SMKN, with totalsample was 120 students and 5 guidance and counseling teachers which wasseleted by using random technique. By using questionnaires and interview the data of this research was collected and then analyzed by using descriptive statistical techniques.The research results showed that: (1) grouping the students based on their smoking behavior was non-smoker group, hesitated group, and smoker group with the highest number is non-smokers, second place was hesitated, and the last is the smoker group. (2) the scores of the first variable showed that the condition in SMAN is higher than SMKN; second variable scores showed that the condition in SMAN is higher than SMKN, and the third variable scores showed that the condition in SMAN student is higher than SMKN student’s; the relation between three variable scores is high; (3) efforts to prevent student smoking behavior by guidance and counseling teachers in using informasion services was not running well.